A Comparative Lipidomic Analysis of Wild Rice Versus White and Brown Rice. (7th June 2021) - Mosher, Wes; Chen, Chi
Abstract: Objectives: As a staple food in the Native American diet, wild rice ( Zizania spp.) is an edible grass native to the Great Lakes region. Wild rice contains about one % of lipids. Previous studies have determined its fatty acid composition, but the composition of its lipidome was not examined in detail. This study sought to examine the lipidome of wild rice and provide a comparison to the lipidomes of white and brown rices. Methods: In this study, lipid fractions of six commercially available wild rice samples ( Zizania spp.), one traditionally-harvested wild rice sample ( Zizania spp.), three white rice samples ( Oryza spp.), and three brown rice samples ( Oryza spp.) were extracted by hexane and ethyl acetate, dried in nitrogen gas, and then reconstituted in n-butanol for liquid chromatography-mass spectrometry (LC-MS)-based lipidomic analysis. Multivariate data analysis was performed using principal components analysis and orthogonal partial least squares-discriminant analysis. Models visualized the distinguishing features of each rice and provided information for a database search of selected markers and subsequent comparison to authentic standards. Results: The multivariate model constructed by the LC-MS data of these samples showed clear separation of wild rice samples from white and brown rice samples, suggesting different lipid profiles of wild versus white and brown rice. Wild rice contained higher abundances of linolenic acid-containing triacylglycerol species, but less palmitic acid- and stearic acid-containing triacylglycerol species. Subtle differences between wild rice harvested in Minnesota versus wild rice harvested outside of Minnesota were also observed through lipidomic comparison. Interestingly, 10-demethylsqualene emerged as a prominent feature separating wild rice from white and brown rice through specific analysis of the phytosterol content of wild rice. Conclusions: LC-MS-based lipidomic analysis of in-tact triacylglycerol species as well as a comprehensive profiling of the wild rice lipidome in comparison to that of white and brown rice was performed. These insights provide a compelling rationale for increasing consumer awareness of the benefits of wild rice consumption. Funding Sources: W. Mosher was supported by the University of Minnesota CFANS Diversity Scholars Fellowship.